Early and late operation of cleft lip and intelligence quotient and psychosocial development in 3-7 years - Petráčková, Irena; Zach, Jiří; Borský, Jiří; Černý, Miloš; Hacklová, Renata; Tvrdek, Miroslav; Janota, Jan (Early human development, 2015)
BACKGROUND: Early and late operations of the cleft lip represent exposure to general anesthesia during the first year of life. The early exposure to the anesthetics may influence long term neurological outcome. Timing of the operation may also influence the quality of life as babies with early repair might be accepted better by their families. AIMS: The aim of the study was to compare outcomes between two groups of patients operated on for the cleft lip in the first year of life. STUDY DESIGN: Observational cohort study. SUBJECTS: Early repair group included patients operated on in the first eight days of life and late repair group those operated on between 3 and 10 months. OUTCOME MEASURES: Intelligence quotient (IQ) and psychosocial development of children who were operated on for cleft lip were compared at the age of 3-7 years. RESULTS: No differences were found between early (n=15) and late (n=17) repair group in terms of IQ. In both IQ was within the normal range: 100.00 (SD 13.867), 98.76 (SD 10.109), respectively. Significantly better results in physical functioning (P=0.042) and self-esteem (P=0.014) concepts in early repair group were found. CONCLUSIONS: We compared outcomes of two groups of patients operated on for cleft lip in the first year of life. The earlier anesthesia did not show a negative impact on intelligence quotient in 3-7 years compared to later anesthesia. The earlier repair of the cleft lip showed a significant positive impact on psychosocial development in 2 out of 13 concepts tested.
Keywords: Anesthesia, General; stomatochirurgické výkony; Male; Child Development; vývoj dítěte; rozštěp patra; Infant; Age Factors; mužské pohlaví; Intelligence Tests; inteligenční testy; celková anestezie; Oral Surgical Procedures; Intelligence; lidé; ženské pohlaví; Humans; inteligence; kojenec; věkové faktory; Cleft Palate; Female